De- and re-differentiation of the melanocytic lineage - Larribere, Lionel; Utikal, Jochen (European journal of cell biology, 2014)
Terminally differentiated cells can be reprogrammed by the transient, ectopic overexpression of different sets of genes into induced pluripotent stem cells (iPSCs). This process not only has considerable implications for regenerative medicine but is also highly relevant to multiple stages of oncogenesis, including melanoma. In other settings, the de-differentiation of normal and tumor cells is also responsible for a phenotype switch which completely changes the cell fate. Conversely, iPSCs as well as embryonic stem cells (ESCs) can be differentiated in vitro toward specific lineages, for example melanocytes, which offer useful models to investigate the genetic and epigenetic mechanisms involved in cellular differentiation. Here, we summarize recent findings regarding the reprogramming and de-differentiation of melanocytic cells as well as the latest differentiation protocols of pluripotent stem cells into the melanocyte lineage.